Integration of emerging motion capture technologies and videogames for human upper-limb telerehabilitation: A systematic review (2015)
Integrating emerging technologies has shown to have the potential to improve access to rehabilitation services and the adherence for physical therapy when they are applied into telemedicine environments. This systematic review aims to explore telerehabilitation systems that use motion capture and video games for upper-limb rehabilitation purposes. Motion capture was focused on the information fusion from inertial sensors and other technologies. The search was limited to 2010-2013, from which 667 papers were obtained; afterwards, duplicate papers were removed, thus, reducing the sample to 57 papers with full text availability. Finally, only 3 of them were selected by approaching the subject of this study. We conclude that the fusion information from inertial sensors and other motion capture technologies appears to be a new tendency in remote monitoring of motor rehabilitation process. However, the combination of them with active video games in physiotherapy programs is only an emerging research area with promising results.